KOMPUTASI METODE SIMPLEKS PADA PENYELESAIAN PROGRAM LINIER - Ahmad Yusuf; Dewi Sri Susanti (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2010)
One of the methods that can be used to solve linear program problem is a simplex method. In this study, researchers will try to make a computational algorithm the simplex method that can be used for the completion of the linear program, so obtained a series of efficient completion processes and optimal end results. This research generate program code Computing using Borland Delphi 6.0 programming language which can be used to solve linear program problems by using simplex method.